Socialism and Religion of Paul Tillich (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aims to clarify the socialistic idea and religion at the theological philosopher Paul Tillich, and the ability of this philosopher on the twinning of the social: state that is moving toward the collective intellect, which is trying to defend the proletariat rights, with the religious situation, especially Protestantism to which he belongs, and which emphasizes the individual propensity in the faith issue, in addition to his affiliation existential stream, which emphasizes the individual case, Protestantism has formed a religious cover for social and economic variety emerging at the time of the wreck of feudalism and aristocracies, which are no longer express themselves religiously, has the Church indulged all those who made it, in the hand is placed on the worldly things, and moved away from religious matters, prompting the curse of the oppressed people, especially the proletariat, which was crushed, is able to cover the new requirements to meet the situation arising? Will was able to win the heart of the proletariat? Here we will show a new form, Tillich tries to submit a religious socialism to which he belongs, Is this socialism was able to overcome the pitfalls of previous socialist them? In this research, we will try to answer those questions.يسعى هذا البحث إلى توضيح فكرة الاشتراكيّة والدين عند الفيلسوف اللاهوتي بول تيليتش، ومدى قدرة هذا الفيلسوف على توأمة الحالة الاشتراكيّة التي تتجه نحو الفكر الجمعي، والتي تحاول الدفاع عن حقوق الطبقة العاملة، مع الحالة الدينيّة وخاصة البروتستانتيّة التي ينتمي إليها، والتي تؤكد على النزوع الفردي في المسألة الإيمانيّة، بالإضافة إلى انتمائه للتيار الوجودي الذي يؤكد الحالة الفرديّة، فقد شكلت البروتستانتيّة غطاءً دينيّاً للتشكيلة الاجتماعيّة والاقتصاديّة التي نشأت في ذلك الوقت من حطام الاقطاعيّات والأرستقراطيّات، التي لم تعد تعبر عن ذاتها دينيّاً، فقد انغمست الكنيسة وكل القائمين عليها، في وضع اليد على الأمور الدنيويّة، مبتعدةً عن الأمور الدينيّة، مما أثار عليها نقمة الناس المضطهدة، وخاصة الطبقة العاملة التي كانت مسحوقة، فهل استطاع الغطاء الجديد تلبية متطلبات الحالة الناشئة؟ وهل استطاع أن يكسب ود الطبقة العاملة؟ هنا سيظهر لنا شكل جديد يحاول تيليتش تقديمه وهو الاشتراكيّة الدينيّة التي ينتمي إليها، فهل هذه الاشتراكيّة استطاعت تخطي عثرات الاشتراكيّات السابقة عليها؟ سنحاول في هذا البحث الإجابة على تلك الأسئلة المطروحة.